Positive Psychology, Indian Psychology and Spirituality - PRIYANKA SHUKLA (Dr. Chinmay Pandya, 2016)
Positive psychology is a relatively new field that examines how ordinary people can become happier and more fulfilled. Positive psychology is a science of positive aspects of human life, such as happiness, well-being and flourishing. Indian psychology is an approach to psychology based on the Indian ethos. Indian Psychology is essentially positive and rooted in the consciousness-based Indian worldview, yoga and a life-affirming spirituality. Human life is a journey of the soul which resides in the human body. Indian psychology highlights the pathway to make this journey easy and the ultimate goal of liberation of the soul (moksha) achievable through yoga, meditation and prayer. Humans are made of the body, mind, intellect, ego and soul and only soul can help to attain ultimate happiness and bliss through spirituality. The present paper is an attempt to explain that both positive psychology and Indian psychology focus on human happiness and their unique strength; and discusses how goals of positive psychology can be achieved through the rich Indian spiritual heritage. Indian psychology and spirituality share a framework that human has enormous potential hidden in its being. Indian scriptures (Vedas, Upanishads, Yoga, Bhagavad Gita) and spiritual practices (Yoga, meditation and prayer) help to discipline the mind to achieve balance, (samyavastha) to overcome the hindrance in the pursuit of happiness and to improve the qualities of different roles we play in our lives. In this way the Indian spiritual practices have important implications for the achievement of goals of Positive Psychology i.e. wisdom and knowledge, courage, humanity, justice and transcendence and makes life worth living.